2002
DOI: 10.1523/jneurosci.22-22-09698.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Distribution and Functional Expression of Small-Conductance Ca2+-Activated K+Channels in Rat Brain

Abstract: Small-conductance Ca 2ϩ -activated K ϩ (SK) channels are important for excitability control and afterhyperpolarizations in vertebrate neurons and have been implicated in regulation of the functional state of the forebrain. We have examined the distribution, functional expression, and subunit composition of SK channels in rat brain. Immunoprecipitation detected solely homotetrameric SK2 and SK3 channels in native tissue and their constitutive association with calmodulin. Immunohistochemistry revealed a restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
217
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(239 citation statements)
references
References 43 publications
16
217
2
1
Order By: Relevance
“…Preliminary results suggest that serotonergic (5-HT) and cholinergic (Maler et al, 1981;Phan and Maler, 1983) input to the ELL can regulate bursting (Ellis, unpublished observations), although direct links to SK channels have not yet been established. The fact that cortical pyramidal cells strongly express SK2 channels (Stocker and Pedarzani, 2000;Sailer et al, 2002;Villalobos et al, 2004) and that at least a subset of these are bursty, suggests that similar mechanisms to those described here may be operative in the control of velocity tuning of pyramidal cells in visual cortex (Priebe et al, 2006). Direct evidence with regard to SK channel control of frequency tuning is currently lacking for mammalian neurons expressing SK channels (including cortical pyramidal cells).…”
Section: Discussionmentioning
confidence: 58%
“…Preliminary results suggest that serotonergic (5-HT) and cholinergic (Maler et al, 1981;Phan and Maler, 1983) input to the ELL can regulate bursting (Ellis, unpublished observations), although direct links to SK channels have not yet been established. The fact that cortical pyramidal cells strongly express SK2 channels (Stocker and Pedarzani, 2000;Sailer et al, 2002;Villalobos et al, 2004) and that at least a subset of these are bursty, suggests that similar mechanisms to those described here may be operative in the control of velocity tuning of pyramidal cells in visual cortex (Priebe et al, 2006). Direct evidence with regard to SK channel control of frequency tuning is currently lacking for mammalian neurons expressing SK channels (including cortical pyramidal cells).…”
Section: Discussionmentioning
confidence: 58%
“…These values were not different from one another (two-way ANOVA: F (2, 60) = 0.688, p = 0.507), suggesting that in lOFC neurons, gluconate containing internal solutions do not affect SK currents at least during the time of recording (o5 min). Previous studies have reported the expression of three distinct subunits of SK channels throughout the brain (Sailer et al, 2002(Sailer et al, , 2004. In the cerebral cortex, SK1 is highly expressed in layer I to V with minimal expression in layer VI.…”
Section: Wd From Cie Suppresses the Functional Activity Of Small Condmentioning
confidence: 99%
“…Cells were then washed three times with phosphate-buffered saline for 5 min, both before and after a 4-hr incubation with the anti-SK3-specific antibody that reacts with the N terminus of full-length SK3 (Alomone Labs), and following a 1-h incubation with the secondary Alexa-594-conjugated goat-anti-rabbit Ig antibody (Molecular Probes). Antibodies specific for the C termini of rodent SK3 were gifts from Dr. Hans-Gunther Knaus (Innsbruck, Austria) (17) and Dr. Martin Stocker (University College London).…”
Section: ј-Race-mentioning
confidence: 99%
“…Recent quantitative RT-PCR studies have identified SK3 transcripts in other human tissues including the trachea, thyroid, spleen, and thymus (16). In the brain, SK3 is restricted to the midbrain monoaminergic neurons, basal ganglia, and limbic system, showing little overlap with SK1 and SK2 (7,13,14,16,17), and recent immunohistochemical studies have localized SK3 to presynaptic nerve termini (18). The SK3 channel serves as the intrinsic pacemaker in dopaminergic neurons and its pharmacological blockade leads to bursting action potentials and increased dopamine release (4, 19 -21).…”
mentioning
confidence: 99%